PENGARUH EFEKTIVITAS SISTEM INFORMASI AKUNTANSI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DENGAN INSENTIF SEBAGAI PEMODERASI - Dewa Ayu Suci Candra Dewi; Ni Wayan Alit Erlina Wati (Hita Akuntansi dan Keuangan, 2021)
The companies expects employee for finished tasks and produce information in a timely, accurate, and reliable manner. This research aims to determine the effect of the effectiveness of accounting information system & work motivation on employee performance with incentives as moderating. This research uses primary data collected through a questionnaire as an data collection techniques and is distributed to respondents. This research was conducted at Rural Bank in Klungkung Regency amounting to 145 employees using purposive sampling technique and the number of samples obtained was 50 employees. The respondents of this study were the internal supervisors, the credit and marketing department, funds department, and the accounting department. Moderated regression analysis is analysis technique used. Based on results of data analysis it was found that the effectiveness of accounting information systems & work motivation has a positive effect on employee performance and incentives weaken the effect of the effectiveness of accounting information systems & work motivation on employee performance.